2024
DOI: 10.1128/aem.01756-23
|View full text |Cite
|
Sign up to set email alerts
|

The biotechnological potential of the Chloroflexota phylum

André Freches,
Joana Costa Fradinho

Abstract: In the next decades, the increasing material and energetic demand to support population growth and higher standards of living will amplify the current pressures on ecosystems and will call for greater investments in infrastructures and modern technologies. A valid approach to overcome such future challenges is the employment of sustainable bio-based technologies that explore the metabolic richness of microorganisms. Collectively, the metabolic capabilities of Chloroflexota , spannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 139 publications
(149 reference statements)
1
0
0
Order By: Relevance
“…This suggested that Anaerolineae should be introduced to the reactor with anammox enrichment, likely ruling out its role in anaerobic ethane oxidation. Indeed, Anaerolineae was frequently detected in wastewater samples, similar to our inoculum sources. This Anaerolineae class has been reported to be strictly anaerobic chemoorganotrophic and contribute to decomposition of dissolved organic matter, indicating Anaerolineae may also be able to use organic intermediates.…”
Section: Resultssupporting
confidence: 69%
“…This suggested that Anaerolineae should be introduced to the reactor with anammox enrichment, likely ruling out its role in anaerobic ethane oxidation. Indeed, Anaerolineae was frequently detected in wastewater samples, similar to our inoculum sources. This Anaerolineae class has been reported to be strictly anaerobic chemoorganotrophic and contribute to decomposition of dissolved organic matter, indicating Anaerolineae may also be able to use organic intermediates.…”
Section: Resultssupporting
confidence: 69%